Association between Clinical Features and Risk Factors for Breast Cancer through a Cross-Sectional Study (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Breast cancer was responsible for 685,000 deaths worldwide in 2020. Approximately half of all breast cancers arise in women who have no identifiable risk factors other than their gender and age. Objectives: The goal of this study was to determine the association between clinical features and breast cancer risk factors. Methods: This cross-sectional study was conducted among 50 histologically confirmed breast cancer patients included by purposive sampling technique in the Surgery Department of Rangpur Medical College, Rangpur.Results: The presence of breast lump was significantly associated with the residence of patients (p value